Transformation Management In Educational Institutions: A Qualitative Research - Nurul Fadhilah (Gestion Educativa, 2024)
This research aims to explore and understand change management in educational institutions through a qualitative approach. The main focus of the research is on the processes, challenges and strategies implemented by stakeholders in dealing with change. Data were collected through in-depth interviews with principals, teachers and administrative staff in various educational institutions. The results of the analysis show that change management in educational institutions is influenced by factors such as leadership, organizational culture, communication, and active participation from all members of the organization. The findings reveal that adaptive leadership and effective communication are critical in facilitating successful change. In addition, the involvement of teachers and staff in the decision-making process strengthens the sense of ownership and commitment to the change. This study provides valuable insights for education practitioners and policy makers in developing more effective change management strategies in educational settings.